A Risk and Hazard Analysis Model for the Production Process of a New Meat Product Blended With Germinated Green Buckwheat and Food Safety Awareness - Atambayeva, Zhibek; Nurgazezova, Almagul; Rebezov, Maksim; Kazhibayeva, Galiya; Kassymov, Samat; Sviderskaya, Diana; Toleubekova, Sandugash; Assirzhanova, Zhanna; Ashakayeva, Rysqul; Apsalikova, Zukhra (Frontiers in Nutrition, 2022)
This research was specifically designed for a small-scale meat processing enterprise “DARIYA” to set up a specific HACCP plan for the new product (patties) made from mixed horsemeat with vegetable components developed in the Department of Technology of Food Production and Biotechnology, Shakarim University of Semey. Critical control points (CCPs) were identified and applied in the HACCP plan. The different hazards were detected at each processing step, whereas each CCP in the HACCP plan is identified and accompanied with the appropriate significant hazard, critical limit, monitoring of the CCP and corrective actions, and confirming that the enterprise has fully employed the HACCP methodology and ISO 22000:2018. Our results indicate that during almost one year following the implementation of ISO 22000:2018, the coliforms level of tested patties significantly dropped (p<0.05) after six months of implementation (coliform count dropped from 4.4 MPN/g to 1.8 MPN/g). The rapid screening of the bacterial count, heavy metals, pesticide residue, and physical contaminations levels also improved monitoring assertiveness allowing deal with foreseeable issues linking to resources and guaranteeing product quality. Cesium-137 was recorded as 5.4 ±2.9627 Bq/kg in horsemeat and 6.7±2.7045 in poultry. The activity of cesium-137 did not exceed the MAC. This result discloses that prompt screening is the foremost and necessary step for small enterprises. According to a current study the “Acceptance of raw materials” is the most important CCP, and their control, particularly in small-scale meat processing enterprises, can actually prevent many negative outcomes. The implementation of both standards improved food quality by declining the flaw rates for patties, and the number of flow inconsistencies needed correction in the process also dropped significantly (p<0.05), demonstrating that safety and quality points were improving. If the application of the HACCP plan were to continue over an extended period of time, the Food Safety Management System’s (FSMS) benefits would be more substantial improvements to a greater number of items being monitored. The process of implementing HACCP principles and ISO 22000:2018 could be arduous but achievable to be used in small industries with significant outcomes.